Energy Cycle Optimization of Mobile Phones Using A Sleep Cycle Optimization Algorithm - Murawwat, S.; Manzoor, I.; Akash, H.; Ahmed, J. (Engineering, Technology & Applied Science Research, 2019)
Researchers and mobile network operators are dealing with the steep rise in energy consumption of mobile phones. A massive amount of phones are available in the market which are updating services from time to time. The problem lies in their battery drainage in response to the usage of internet-based applications including online streaming, multimedia requests, social networking usage and many more. In this research, a new technique is proposed and evaluated for energy optimization in mobile phones by exploiting the listening cycle of the mobile station (MS) wake-up mode while connected to the base station (BS) that is connected to a mobile network based on IEEE 802.16e. An MS cannot communicate with the BS if it is in the sleep mode while the other is in the wake-up mode. Service time and sojourn time are assumed to be exponential and based on t-distribution. The confidence interval comes up to 95% for our technique. The relative error is computed between the earlier techniques available and the approximated proposed one. Results show that there is a considerable improvement in energy consumption as compared to the other available techniques.